Modern family - Cheon, Myung-Kwan. (Korean voices series ;, 2015)
Forty-year-old In-mo, a movie director who's been jobless for the past decade decides to move in with his widowed mother. His older brother, with five criminal convictions, has already moved back. Then younger sister Mi-yeon arrives with her bratty, rebellious fifteen-year-old daughter. Mom is delighted to have her entire dysfunctional family back again, but what ensues is both comic and frightening